2014
DOI: 10.2463/mrms.2014-0016
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Diffusion MR Imaging Data using a Gamma Distribution Model

Abstract: Purpose: Although many models have been proposed to interpret non-Gaussian diffusion MRI data in biological tissues, it is often difficult to see the correlation between the MRI data and the histological changes in the tissue. Among these models, so called statistical models, which assume the diffusion coefficient D is distributed continuously within a voxel, are more suitable for interpreting the data in a histological context than others. In this work, we examined a statistical model based on the gamma distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 9 publications
1
36
0
Order By: Relevance
“…A statistical comparison of the curve fits between the gamma model and the truncated Gaussian model was performed on PCa, BPH, and healthy PZ by F tests using R 2 values of each fit. In addition, the parameters of the gamma model [mean ( α / β ), standard deviation ( α/β2), the area fraction of D < 1.0 mm 2 /s (Frac<1.0), the area fraction of D > 3.0 mm 2 /s (Frac>3.0)], which were proposed in the previous study , and the truncated Gaussian model ( D m , σ, Frac<1.0, and Frac>3.0) were compared between PCa, BPH, and healthy PZ using a one‐way analysis of variance (ANOVA). Post‐hoc Tukey–Kramer tests for pairwise comparisons were used to determine whether there was any significant difference between PCa, BPH, and healthy PZ (MedCalc, v. 11.6.2.0, MedCalc Software, Mariakerke, Belgium).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A statistical comparison of the curve fits between the gamma model and the truncated Gaussian model was performed on PCa, BPH, and healthy PZ by F tests using R 2 values of each fit. In addition, the parameters of the gamma model [mean ( α / β ), standard deviation ( α/β2), the area fraction of D < 1.0 mm 2 /s (Frac<1.0), the area fraction of D > 3.0 mm 2 /s (Frac>3.0)], which were proposed in the previous study , and the truncated Gaussian model ( D m , σ, Frac<1.0, and Frac>3.0) were compared between PCa, BPH, and healthy PZ using a one‐way analysis of variance (ANOVA). Post‐hoc Tukey–Kramer tests for pairwise comparisons were used to determine whether there was any significant difference between PCa, BPH, and healthy PZ (MedCalc, v. 11.6.2.0, MedCalc Software, Mariakerke, Belgium).…”
Section: Methodsmentioning
confidence: 99%
“…They proposed a truncated Gaussian-type function, restricted to positive ADC values, as the distribution of ADCs. Recently, we reported that the gamma function provided a better fit than the truncated Gaussian function as a distribution function for ADCs using a clinical dataset from histologically proven prostate cancer (16,17). The b-values used for the latter study were within the 0 to 1000 s/mm 2 range; however, the non-monoexponential diffusionrelated signal decay generally becomes more apparent over more extended b-value ranges (8,9,18).…”
mentioning
confidence: 97%
“…Several groups of methods have been proposed for modeling the dMRI signal acquired using a standard single diffusion encoding (SDE) experiment (Basser et al, 1994; Assaf et al, 2002; Jensen et al, 2005; Schultz et al, 2014; Özarslan et al, 2009; Morozov et al, 2014; Huang et al, 2015). A large family of methods focus on estimating the ensemble average propagator (EAP) of the diffusing spins under the narrow pulse approximation (Cheng et al, 2010; Merlet and Deriche, 2013; Özarslan et al, 2013; Scherrer et al, 2013; Rathi et al, 2014; Ning et al, 2015; Ghosh and Deriche, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Another approach is the application of the gamma function to the statistical distribution of ADC values: the gamma distribution (GD) model . This model is expected to reflect the probability of the distribution of water molecule mobility in different regions of the tissue .…”
mentioning
confidence: 99%
“…This model is expected to reflect the probability of the distribution of water molecule mobility in different regions of the tissue . Based on this statistical approach, one can also obtain the fraction of intracellular, extracellular, and perfusion components of tissue . All this information, obtained through only one model, may surpass the advantages offered by other models.…”
mentioning
confidence: 99%